Parents' and kids' eating away from home cognitions. Issue 5 (25th April 2019) - Eck, Kaitlyn M.; Delaney, Colleen; Olfert, Melissa D.; Hagedorn, Rebecca L.; Leary, Miriam P.; Santella, Madison E.; Clark, Rashel L.; Famodu, Oluremi A.; Shelnutt, Karla P.; Byrd-Bredbenner, Carol
Abstract : Purpose: Eating away from home frequency is increasing and is linked with numerous adverse health outcomes. The purpose of this paper is to inform the development of health promotion materials for improving eating away from home behaviors by elucidating related parent and child cognitions. Design/methodology/approach: Parents ( n =37) and children ( n =35; ages 6–11 years) participated in focus group discussions, based on social cognitive theory. Data were content analyzed to detect themes. Findings: Many parents were concerned about what children ate away from home, however, others were less concerned because these occasions were infrequent. Lack of time and busy schedules were the most common barriers to eating fewer meals away from home. The greatest barrier to ensuring children ate healthfully away from home was parents were not present to monitor children's intake. To overcome this, parents supervised what kids packed for lunch, provided caregivers instruction on foods to provide, and taught kids to make healthy choices. Kids understood that frequently eating away from home resulted in less healthful behaviors. Barriers for kids to eat healthy when away from home were tempting foods and eating in places with easy access to less healthy food. Kids reported they could take responsibility by requesting healthy foods and asking parents to help them eat healthfully away from home by providing healthy options and guidance. Originality/value: This study is one of the first to qualitatively analyze parent and child eating away from home cognitions. It provides insights for tailoring nutrition education interventions to be more responsive to these audiences' needs.